The post-national and the return to nationalism in The peasants’ war panorama by Kathrin Röggla - Endreva, Мaria (Journal for German and Scandinavian Studies / Списание „Германистика и скандинавистика“, 2025)
The text analyzes Röggla’s Bauernkriegspanorama and in a systematization of the various topics in the essay attempts to justify the main thesis that post-nationalism with its wild commodification of life is reactivating the forces of nationalism that were believed to be dead. First, the negative effects of economic globalization are pointed out, which lead to insecurity in people and to the glorification of the past as a subject of nostalgia, and finally the role of the writer as the creator of new perspectives is discussed.
Keywords: Kathrin Röggla; post-nationalism; Bauernkriegspanorama; globalisation; Austrian literature